2003
DOI: 10.1093/sleep/26.7.878
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Predictors of Sleepiness Correlated with the Multiple Sleep Latency Test in an Asian Singapore Population

Abstract: The Epworth Sleepiness Scale and apnea-hypopnea index are useful predictors of sleepiness in our Asian Singapore population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…We found that patients with higher AHI, more severe oxygen desaturation or more fragmented sleep tended to have higher ratings of daytime sleepiness. The findings were consistent with previous studies [19, 20]. …”
Section: Discussionsupporting
confidence: 94%
“…We found that patients with higher AHI, more severe oxygen desaturation or more fragmented sleep tended to have higher ratings of daytime sleepiness. The findings were consistent with previous studies [19, 20]. …”
Section: Discussionsupporting
confidence: 94%
“…The distribution of ESS scores was also skewed and the threshold matched with the 25th percentile score. In the previous study, an ESS of ≥8 reliably predicted sleep latency of less than 10 min on the multiple sleep latency test [34]. Sleep duration was categorized into five groups (<6, 6-7, 7-8, 8-9, and ≥9 h).…”
Section: Discussionmentioning
confidence: 96%
“…The finding suggests that daytime sleepiness might impair sustained attention even at the degree of sleepiness below the level of "excessive" sleepiness. An ESS of ≥8 reliably predicted a moderate degree of daytime sleepiness on the multiple sleep latency test [34]. One caveat to interpret the correlation between daytime sleepiness and PVT performance is that daytime sleepiness measured by ESS is determined by multiple factors [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The ESS has been found to be a valid and reliable tool to separate normal adult subjects from patients with sleep disorders (Johns, 1991,Pallesen, et al, 2007). Studies have shown that ESS scores correlate at least moderately with objective measures of sleepiness (Cai, et al, 2013,Johns, 1991,Leng, et al, 2003). Scores range from 0–24.…”
Section: Methodsmentioning
confidence: 99%